2014
DOI: 10.1051/epjap/2013130517
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photovoltaic conversion efficiency in bulk heterojunction solar cells upon incorporating nanohybridized PbS quantum dots/multiwall carbon nanotubes

Abstract: Abstract. We report on a modified bulk heterojunction (BHJ) solar cell in which a nanohybridized composition of lead sulfide (PbS) colloidal quantum dots (QDs) and multiwall carbon nanotubes (MWCNTs) were incorporated into a standard regioregular poly(3-hexylthiophene) (rr-P3HT):phenyl-C61-butyric acid methyl ester (PCBM) blend. This hybrid ((P3HT:PCBM):PbS-QD/MWCNT) solar cell exhibits an increased power conversion efficiency (PCE) of 3.40% as compared to that of 2.57% from a controlled P3HT:PCBM standard BHJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 48 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…The figure shows that the maximum absorption wavelength is in the range of 400 -1100 nm, which is mean the network absorbed the spectrum in Vis-NIR region. This result in agreement with [11]. Many sharp peaks have appeared in the absorbance spectrum, such as 400, 475, 525, 750, 800, 850, 950 and 1100 nm, respectively, these peaks may be attributed to the network structure as a mat.…”
Section: Resultssupporting
confidence: 89%
“…The figure shows that the maximum absorption wavelength is in the range of 400 -1100 nm, which is mean the network absorbed the spectrum in Vis-NIR region. This result in agreement with [11]. Many sharp peaks have appeared in the absorbance spectrum, such as 400, 475, 525, 750, 800, 850, 950 and 1100 nm, respectively, these peaks may be attributed to the network structure as a mat.…”
Section: Resultssupporting
confidence: 89%
“…Despite the high theoretical specific capacity of 1672 mA h g –1 and energy density of 2600 W h kg –1 for LSBs, the sulfur in cathodes as the reservoir for lithium faces several problems, including the ionically and electrically insulating effects of sulfur (5 × 10 –30 S·cm –1 at 25 °C), the formation of soluble intermediate polysulfides (Li 2 S x , 4 ≤ x ≤ 8), and a large volumetric expansion upon the formation of Li 2 S. , These problems are reflected in the low rate capacity, low Columbic efficiency, self-discharge, rapid capacity fading, , damages to the material structure, and continuous loss of sulfur . Many research works have been reported concerning these issues. So, embedding as many sulfur as possible into various inorganic, carbon, or polymer , host materials and trapping of polysulfides in these mesoporous host materials are among the prevailing solutions to the problems. Polymers, in this case, are extensively studied as binders, coatings , on sulfur active materials, separator, or electrolyte; ,,, there are limited reports on polymer cathode in LSB. ,, But, when used as cathode materials, polymers are rather promising due to their available structural and electrochemical controlling parameters. …”
Section: Introductionmentioning
confidence: 99%